PENGGUNAAN EKSTRAK DAUN KATUK (Sauropus androgunus L. Merr) SEBAGAI BAHAN PE,NGA-WET ALAMI DAGINGSAPI SEGAR - Bambang Kuntoro; Irdha Mirdhayati, dan; Triani Adelina (Jurnal Peternakan, 2007)
Meat is high nutrient food material because it consist much protein, fat, mineral and other substances that needed by human body. The .Meat nutrient pel'centage is the appropriate media for the growth of microorganism especially bacteria. The microorganism activity can decrease meat quality. Hence, itneed exact treatment for keep the meat quality. One of used the treatment is adding extract of the Sauropus and1'og}Jnus (L.) Me1'1'. Extract of the Sauropus androgynus constitute material that consist of antibacterial compounq. Content OrSO:UT0pu5 androgyrius characteristk is oxide bacteria that having ability to remove son}e bacteria sm;has seskuite,rna add. alkaloid papaVerlllt tanin,.. saponiri,. fiavonoiq, mineral salt, other compounds,The purpose of this research is to determine influence the meat submersion within e)."tract of the Sauropus androgynus to pH, water content, total of bacterial colony, storage endurance and sensorial value include color, tex'ture, and aroma. The research use 2.5 kilogram of ham's beef and extract of the Saurapus andmgynus as much as 240 mI. Experiment method is used in this research by use a Complete Random Design that consist of four treatments with three repeat. The treatments are the extract of the So:uropfls alldrogymes concentration's level consist of ' 0 mI, 10 ml. 20 mI, aud 30 ml. The submersion has. taken as long as 30 ffiillUI:e5. Variables that measured is pH, water content romlof 'bacterial colony, storage endurance and sensorial value of meat. The differences among the treatments have tested by DcJ1nc<.(l1fi l'vl~~h:ipJ;? Range Test(DJVrRT).'fh.e result vf the n.''5eaochshow5 that the submersion of beef within Extract of the Sauropus androgynus (1.) Mm30 in! can decrease pH to 5.17, in~storage'endtn:'am:e about19.33 hours and deerea5€' water content to 73.72% and 1.6 x lOS of total bacterial colony.hQwE"I<"et it cO.rmot influence to serl.sorialvaiu€ (coTe>!', textW:e and aroma). The resultof meat color is nndesired red, the texture have plaited pattern, tugged and not attractive,and m",,anwhile the aroma resulted is putrid taste.